Os autos da querela na capitania do Ceará (1779-1793) - Valente Neto, José (2024)
The history of the administration of criminal justice is a field of study that has not attracted due attention in Brazil. The justifications oscillate between the quantity and quality of the sources and the late development of criminal law in legal dogmatics. If, on the one hand, the scarcity of lines of research at universities is one of the results of this situation, on the other, the work carried out demonstrates the relevance of this branch of knowledge as a privileged tool for understanding power dynamics both in slavers and non-slavers societies. In effect, criminal law functioned as a mechanism for repressing and maintaining inequalities and stratified hierarchies in the context of slavery and, with different logics, also as an instrument of social control in spaces that prohibited slavery. When looking from the perspective of centers and peripheries in a colonial economic and political context, slave and non-slave societies were interconnected in different ways, including through criminal law. In this sense, whether as a threat of punishment or as an effective practice of imposing discipline, it was crucial both in the relationship between Victorian England and the post- independence United States of America and between Portugal and Portuguese America. Its role in the Modern Age was strategic because it maintained a series of functions in various instances of power and acted both in the center and, subsidiarily, on the margins of overseas empires. The object of the research is the analysis of one of the Captaincies of North Portuguese America: “Siará Grande”. The central question of the work is: what were the uses of criminal justice in the Captaincy of Ceará Grande in the second half of the 18th century? The methodology used had as its starting point the study of 66 records of disputes and denunciations registered in the Captaincy of “Ceará Grande” between 1779 and 1793. These manuscripts are in the Public Archive of the State of Ceará and, for the preparation of the thesis, the transcription was kindly provided by Prof. Dr. Expedito Eloísio Ximenes, from the Literature Course at the State University of Ceará. In addition to examining primary sources, books, articles, theses and dissertations were read. The information extracted from the documents and bibliography allows us to affirm that the sphere of justice in the Captaincy's villages was a relevant space for negotiation and conflict resolution.